Hermeneutika Kidung Pantun Sunda - Wiradiredja, M. Yusuf (Paraguna, 2021)
Cultural expression, especially art, in many ways has a very strong relationship with the cosmology, space, or environment in which expression is born. In other words, cultural products, especially works of art that are rarely affected by the surrounding natural conditions. In the context of a popular Sundanese song, it is impossible for Koko to compose the song "Malati di Gunung Guntur", without seeing the natural reality of the mountains and their beautiful contents so as to produce a song that has aesthetic value. This is also the case with the artistic expressions of the old people, especially in wayang golek performances which are closely related to the concept of the mountain for the Sundanese people, including, and especially in this article, the song "nataan gunung" in the wanda Papantunan in the Sundanese song Cianjuran, with the presence of mountains. in the land of Sunda. Interpreting the correlation between art and nature, especially the relationship between the Sundanese people and the mountains, can be seen by deepening the interpretation, especially with how the Sundanese people position or place mountains in life that express artistic expressions. This paper is an attempt at hermeneutical interpretation of the Sundanese rhyme song entitled "nataan gunung" which is seen in a paradigmatic way with its relationship with gunungan wayang.